Free Shipping Promotions and Product Returns - Shehu, Edlira; Papies, Dominik; Neslin, Scott A. (Journal of Marketing Research, 2020)
Free shipping promotions have become popular among online retailers. However, little is known about their influence on consumers’ purchases, return behavior, and, ultimately, firm profit. The authors propose that free shipping promotions encourage customers to make riskier purchases, leading to more product returns. They estimate the impact of these promotions on purchase incidence, high-risk and low-risk spend, and return share. The results show that free shipping promotions increase expenditure for high-risk products, expanding their share of the consumer’s market basket and thus increasing the overall return rate. This is validated in a field experiment. A field test and an online lab experiment analyze the mechanism linking free shipping and returns. The results suggest that the free shipping effect occurs through consumers’ perceptions that free shipping serves as a risk premium compensating them for potential returns and through positive affect generated by the promotion. A simulation shows that for the focal firm, free shipping promotions increase net sales volume, but higher product returns and lost shipping revenue render these promotions unprofitable.